Answer:
The correct answer is B. {-9/11}
Explanation:
1. Let's solve the linear equation:
x-6/-3 + x+9/9 = x+4
-3(x - 6) + x + 9 = 9 (x + 4) (Multiplying by 9 at both sides)
-3x + 18 + x + 9 = 9x + 36
-3x + x - 9x = 36 - 18 - 9 (Like terms)
-12x + x = 36 - 27
-11x = 9
x = -9/11
2. Let's prove that x = -9/11 is correct
x-6/-3 + x+9/9 = x+4
(-9/11 - 6)/-3 + (-9/11 + 9)/9 = -9/11 + 4
(-75/11 * - 1/3) + (90/11 * 1/9) = -9/11 + 44/11
25/11 + 10/11 = 35/11
35/11 = 35/11
We proved that x = -9/11 is correct.